Neutrophil to lymphocyte ratio and Platelet to lymphocyte ratio: Novel markers of inflammation in Psoriasis - Yadav, Shakti Kumar; Sharma, Santosh; Singh, Sompal; Khurana, V K; Sarin, Namrata (Annals of Pathology and Laboratory Medicine, 2019)
Background: Psoriasis is a systemic, autoimmune chronic inflammatory disease. Novel inflammatory biomarkers like neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) may help in evaluation of systemic inflammation. Aim of the present study was to evaluate NLR and PLR in patients of psoriasis and to correlate them with psoriasis area severity index (PASI) score. Methods: The study was done in a tertiary care hospital. A study was performed with 40 psoriasis patients (study group) and 20 healthy control subjects. Complete hemogram was determined using the 5-part hematology analyser. NLR and PLR values were calculated from the appropriate absolute cell counts. Mann-Whitney U test was applied to compare the data between patients and controls. Pearson correlation was used to find correlation between NLR, PLR and PASI. Result: Mean PLR was 121.79 (42.36) for study group and 101.42 (SD 52.28) for the control group. We found that PLR was significantly higher in study group than the control group (p value = 0.041). There was a positive correlation between PASI and PLR (r=0.476, p value 0.002). We found no difference in NLR values between patients and controls as well as no correlation between PASI and NLR in the study group. Conclusion: PLR can be used as a biomarker to measure and monitor the disease activity in psoriasis patients at the time of diagnosis and follow up. This can also aid in preventing comorbidities in psoriasis patients.